2012
DOI: 10.2903/j.efsa.2012.2737
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of beta‐carotene as a feed additive for all animal species and categories

Abstract: The use of beta‐carotene is safe for the target animals. Setting a maximum content in feed legislation is not considered necessary. However, this conclusion assumes that triphenylphosphine oxide does not exceed 100 mg/kg additive. In all food‐producing animals (except veal calves) and laboratory rodents, beta‐carotene is almost fully metabolised. In contrast, humans, non‐human primates and ferrets absorb relatively high quantities of beta‐carotene unchanged. Investigations with ferrets and hamsters as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The concept that β-carotene is a source of beneficial compounds beyond vitamin A is not new; however, there is a dearth of reproducible evidence as to the identity and biological actions of these compounds. A scientific panel of the European Food Safety Association (EFSA) recently concluded there was insufficient scientific evidence to support a proposed benefit of β-carotene, as a feed additive, on host immunity (EFSA, 2012). The EFSA panel cited an inconsistency of results with β-carotene as the major problem.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that β-carotene is a source of beneficial compounds beyond vitamin A is not new; however, there is a dearth of reproducible evidence as to the identity and biological actions of these compounds. A scientific panel of the European Food Safety Association (EFSA) recently concluded there was insufficient scientific evidence to support a proposed benefit of β-carotene, as a feed additive, on host immunity (EFSA, 2012). The EFSA panel cited an inconsistency of results with β-carotene as the major problem.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, in its assessment of β‐carotene, the Panel determined that the use of supplemental β‐carotene in feeds for food‐producing animals, with the exception of veal calves, would not result in a significant increase in consumer exposure to β‐carotene. The Panel concluded that unlimited use of β‐carotene as an additive to milk replacers used as feed for calves may be of concern as regards consumer safety in those consuming liver from pre‐ruminant calves treated with β‐carotene (EFSA FEEDAP Panel, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on an EFSA (The European Food Safety Authority) scientific opinion (Additives & Feed, 2012), the use of beta-carotene has been found safe in food-producing animals. Therefore, it was not considered necessary to set a maximum content in feed legislation by EFSA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was not considered necessary to set a maximum content in feed legislation by EFSA. Beta-carotene is almost fully metabolized in farm animals (Additives & Feed, 2012). The potential risk of lung and stomach carcinoma associated with beta-carotene supplementation in humans has been highlighted.…”
Section: Introductionmentioning
confidence: 99%